(untitled) (Global Journals of Research in Engineering, 2012)
The aim of this paper is to illustrate the evolution and brief history of Lean and Six Sigma and trace it to its role at present. Also, the paper gives its arguments why they are not mere whims or fads that fade away with the passage of time. The findings in the paper suggest that the implementation of these philosophies of management in industries and other business processes help these enterprises in the reduction of cost and in the of working on improvement of the quality issues. Thus using these two strategies, either individually or together to maximize the gain of an organization may be a logical conclusion. In the present work, we have tried to show that these two strategies are helpful to satisfy cost and quality constraints whether related to products or services and are not just fads, as have been considered to be by some of its critics.